The European Banking Union A Critical Assessment - Baglioni, Angelo; SpringerLink (Online service) (London : Palgrave Macmillan UK(Imprint), 2016)
Why did European policy-makers introduce the Banking Union? Which are its main features? How does it affect banks and their customers? This book tries to answer these questions, by providing a clear description of the building blocks of the Banking Union, and by showing that several issues remain unanswered. The Banking Union is a major step towards a more integrated Europe, thanks to the centralization of the banking supervision. However, it is far from being completed. The author discusses some controversial issues, that still need to be addressed at the policy level, among which are: the cross-country pooling of resources to manage the banking crises, the way to introduce a common deposit insurance scheme, the application of the bail-in rule to the retail bank customers, the methodology to carry out the stress tests on banks, and the attribution of the macro-prudential supervision. .
Keywords: Banks and banking; Capital market